Graphene Oxide Modified Anodic Ternary Nanobioceramics on Ti6Al7Nb Alloy for Orthopedic and Dental Applications. (2017) - Rafieerad, A.R.; Bushroa, A.R.; Nasiri-Tabrizi, B.; Vadivelu, J.; Yusof, F.; Baradaran, S.
Abstract: With increased demands of artificial bone-like tissue specified orthopedic and dental replacement, medical grade of titanium alloys such as Ti6Al7Nb implants (Ti67IMP) have been considered due to their specific density and corrosion resistance with relatively lower moduli than other metals which leads to a better compliance with the modulus of bone. However, without any external force and overloading, the failure might be happen after implantation which need to repeat the surgery step. Thus, in order to minimize the risk of implant loosing and improve biocompatibility, surface modification is required to facilitate the stability of implant trough healing process. The development of nanotubular bioceramics can improve the implants' surface properties and provide rapid osseointegration. It is notified that the considered nanobiomaterials with controlled morphology can effect on antibacterial and drug delivery activities of implants. Herein, mixed oxide nanotubes (titania-niobia-alumina) was fabricated on Ti67IMP using PVD magnetron sputtering and subsequent electrochemical anodization. Initially, a well-adherent niobium (Nb) film was PVD sputtered under optimized coating conditions, then nanotubular arrays were grown on Nb/Ti67IMP surface after subsequent anodization and thermal treatment. In the final stage, the as-prepared graphene oxide (GO) nanosheet was transparently loaded on anodic nanotubes to reinforce ternary ceramic film. The microstructural features, wettability behavior and in-vitro bioactivity of the nanostructured coating were examined. Based on in-vitro bioassay analysis, a thick apatite layer was formed on the implant surface after primary days of immersion in simulated body fluid (SBF).